2011
DOI: 10.1038/ejcn.2011.74
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of lifestyle intervention outcome and dropout: the SLIM study

Abstract: Background/Objectives: To evaluate the effect of a 4.1-year (range 3-6 years) lifestyle intervention according to general public health recommendations on glucose tolerance and dropout in a Dutch population with impaired glucose tolerance (IGT). Subjects/Methods: In the Study on Lifestyle intervention and Impaired glucose tolerance Maastricht, 147 Caucasian IGT subjects were randomized to an intervention group (INT: n ¼ 74; 38 male, 36 female) and control group (CON: n ¼ 73; 37 male, 36 female). Annually, subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 21 publications
5
84
1
2
Order By: Relevance
“…These effects were similar in all racial and ethnic groups and in both sexes. Similar results were observed in independent studies of Asian Indian [30], Dutch [31] and Swedish [32] populations where lifestyle modification was shown to reduce the incidence of DM.…”
Section: Prevention Of Type 2 Dmsupporting
confidence: 88%
“…These effects were similar in all racial and ethnic groups and in both sexes. Similar results were observed in independent studies of Asian Indian [30], Dutch [31] and Swedish [32] populations where lifestyle modification was shown to reduce the incidence of DM.…”
Section: Prevention Of Type 2 Dmsupporting
confidence: 88%
“…Body weight Pooled results of three RCTs [35][36][37][38][39] showed that 1 year of lifestyle interventions was more effective in reducing body weight than treatment as usual. Overall, people with prediabetes receiving lifestyle interventions achieved an additional mean weight reduction of −2.44 kg (95% CI −3.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
“…Seven RCTs with more than 1,200 men and 970 women compared lifestyle interventions with treatment as usual [2,14,15,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][48][49][50][51]. Follow-up periods lasted up to 6 years.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
See 2 more Smart Citations